2019
DOI: 10.3390/nu11030564
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid-Lowering Effects of Combined Glycine and Tryptophan Treatments in Subjects with Mild Hyperuricemia: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study

Abstract: We determined the serum uric acid-lowering effects of combined daily supplementation of glycine and tryptophan in patients with mild hyperuricemia using a randomized, double-blind, placebo-controlled, crossover clinical trial design. Japanese healthy adult males and females with mild hyperuricemia (fasting serum uric acid of 6.6–7.9 mg/dL) ingested a powder mixture containing 3.0 g of glycine and 0.2 g of tryptophan or a placebo powder once daily at bedtime for 6 weeks. Combined supplementation with glycine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…This study examined whether the combined administration of 6.0 g of glycine and 0.4 g of tryptophan suppressed the elevation in serum uric acid levels induced by purine ingestion and increased urinary uric acid excretion. The amino acid doses used for single ingestion were based on those used in continual supplementation [14]. Both glycine and tryptophan are present in dietary proteins that are ingested in normal daily living.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study examined whether the combined administration of 6.0 g of glycine and 0.4 g of tryptophan suppressed the elevation in serum uric acid levels induced by purine ingestion and increased urinary uric acid excretion. The amino acid doses used for single ingestion were based on those used in continual supplementation [14]. Both glycine and tryptophan are present in dietary proteins that are ingested in normal daily living.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous reports [11,12], glycine increased urinary uric acid excretion and enhanced urate clearance in the current study. The authors previously reported that continual supplementation with glycine and tryptophan led to an increase in urinary pH [14]. Glycine exhibits a buffering action and it is often used as an antacid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our two previous clinical trials, the oral administration of the combined dose of glycine and tryptophan led to a decreased concentration of serum uric acid because of the increased urate excretion into the urine [20,21]. A recent prospective cohort study suggested that serum uric acid levels are independently associated with the incidence of impaired renal function and renal progression [22], and a meta-analysis reported that uric acid-lowering therapy effectively regards CKD progression [23].…”
Section: Introductionmentioning
confidence: 95%
“…Uric acid has been found to be strongly associated with triglycerides, regardless of age, sex, smoking, alcohol consumption, obesity and insulin resistance, in a study published in China 26 . Uric acid and triglyceride levels have also been linked to oxidative stress and mitochondrial dysfunction 27 , but there was also a decrease in the level of uric acid and triglycerides following the administration of glycine and tryptophan without diet therapy [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%